Ammonium-to-sodium ion-exchange process at the interlayer of octacalcium phosphate. Issue 62 (13th December 2021) - Sugiura, Yuki; Makita, Yoji; Horie, Masanori
Abstract : Octacalcium phosphate (OCP) has been considered as the layer component of calcium phosphate, but whether it achieves the ionic-exchange ability of conventional layer components is unclear. In this study, we demonstrated the evidence of ionic exchange process at the interlayer of OCP. Abstract : Octacalcium phosphate (OCP) has been considered as the layer component of calcium phosphate, but whether it achieves the ionic-exchange ability of conventional layer components is unclear. As OCP is highly biocompatible, understanding its ionic-exchange properties would potentially expand its pharmaceutical and medical applications. Herein, we demonstrate that the substituted cations in ammonium (NH4 )-substituted octacalcium phosphate (OCP-NH4 ) and sodium (Na)-containing ammonium phosphate solutions undergo ion exchanges with OCP interlayers. Replacing NH4 + with Na + did not alter the crystal structure of OCP, confirming that a substituted cation exchange process similar to that in other layered compounds occurs in OCP.